2021
DOI: 10.1155/2021/5547237
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Challenges of Cloud-Based ERP Adoption in Pakistani SMEs

Abstract: Cloud-based ERP solutions offer many benefits to small and medium enterprises (SMEs) and help them to integrate their activities, such as improve communications and reduce operational and maintenance costs. Primarily, it was only adopted by large organizations, but now SMEs are also keen on adoption. However, the motivation regarding the adoption of these systems in SMEs is relatively low in developing countries. This fact urges us to investigate the challenges faced by Pakistani SMEs. A qualitative research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Lingkungan bisnis UKM telah berubah secara signifikan dalam beberapa tahun terakhir demi kepuasan pelanggan dan fleksibilitas pasar. Berbagai langkah diambil oleh organisasi untuk menghadapi tantangan seperti inovasi model bisnis, peningkatan layanan pelanggan, otomatisasi pekerjaan serta pengembangan sistem TI seperti perencanaan sumber daya perusahaan (ERP) Ini adalah sistem terintegrasi yang dikenal untuk meningkatkan proses dan kualitas produk , mengurangi waktu siklus produksi, dan meningkatkan proses pengambilan keputusan [4].…”
Section: P-issn : 2443-2210unclassified
“…Lingkungan bisnis UKM telah berubah secara signifikan dalam beberapa tahun terakhir demi kepuasan pelanggan dan fleksibilitas pasar. Berbagai langkah diambil oleh organisasi untuk menghadapi tantangan seperti inovasi model bisnis, peningkatan layanan pelanggan, otomatisasi pekerjaan serta pengembangan sistem TI seperti perencanaan sumber daya perusahaan (ERP) Ini adalah sistem terintegrasi yang dikenal untuk meningkatkan proses dan kualitas produk , mengurangi waktu siklus produksi, dan meningkatkan proses pengambilan keputusan [4].…”
Section: P-issn : 2443-2210unclassified
“…Numerous studies have been undertaken to evaluate the benefits and challenges that businesses encounter when implementing cloud ERP in their businesses [9] [18]. Some researchers have concentrated on cloud ERP adoption in various locations such as Europe, the United States, Australia, and Asia [19] [20].…”
Section: B Prior Research Studies In Cloud Erp Adoptionmentioning
confidence: 99%
“…Their study had limitations that it did not consider critical variables such as security and privacy, nor did it take into account the characteristics of decision-makers that could influence cloud adoption. The author in [18] explored the challenges to cloud ERP adoption in Pakistani SMEs using a qualitative methodology in association with unstructured interviews. According to the study, ten potential barriers to the adoption were identified the primary issues to determine whether to accept or reject cloud ERP solutions.…”
Section: B Prior Research Studies In Cloud Erp Adoptionmentioning
confidence: 99%
“…Their study identified that the adoption success of a cloud ERP system depends on innovation characteristics, i.e., relative advantage to current system, compatibility with existing systems, data security and cost of cloud ERP system. Awan et al [31] highlighted that the use of cloud ERP is advantageous to Pakistani SMEs. They highlighted the challenges of adopting cloud ERP system, including customization limitation, data security, awareness, external pressure, vendor competence, lack of knowledge, and resistance to change are the main issues to be mentioned when adopting this system.…”
Section: Adoption Of Cloud Erp In Smesmentioning
confidence: 99%
“…The use of an integrative model to investigate cloud ERP adoption in SMEs is limited, especially focusing on both the organizational and individual levels [e.g., 30,31,32]. Prior studies have investigated adoption of cloud ERP systems in either an organizational or individual context [25].…”
Section: Introductionmentioning
confidence: 99%